Gender behavior in betting markets - Helge Müller; Christoph Schumacher; Eberhard Feess (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We extend gender research on risk behavior to betting markets. Our data set consists of all 5,136,660 bets in New Zealand from 2006 to 2009 and allows assigning each bet to individ-ual bettors. Women are much more prone to the favorite-longshot bias and suffer higher losses. Usually, betting on longshots is associated with higher variance of return, but we find that bet sizes are disproportionally decreasing in odds. Hence, the average risk when betting on longshots is in fact lower. This observation reconciles our findings with gender research on risk preferences and leads to new insights on the favorite-longshot bias.
Keywords: D14; D81; G11; 330; behavioral economics; behavioral finance; gender research; betting markets